Challenges of extraction techniques of natural antioxidants and their potential application opportunities as anti-cancer agents - Mohamed Elnour, Ahmed Adam; Mirghani, Mohamed Elwathig Saeed; Khalid Hamid, Musa; Kabbashi, Nassereldeen Ahmed; Alam, Md. Zahangir (iMed Pub Journals, 2018)
Natural polyphenols (NP) play the vital purpose in malignancy prevention and treatment. NP from medicinal plants (MP) and edible plant include phenolic acids, bioflavonoids, tannins, stilbenes, curcuminoids,coumarins, lignans, quinones, and other folks. Many bioactivities of NP materials are conscientious because of their chemo preventive real estate (e.g., antioxidant, ant carcinogenic, or perhaps ant mutagenic and potent effects) and in addition bring to all their inducing apoptosis by arresting cell interval, regulating carcinogen metabolism and ontogenesis towards inhibiting genes binding and cell consentimiento, migration, growth or difference, and preventing signaling pathways. This analysis covers the modern literature to conclude structural categorizations and molecular anticancer components of phenolic compounds (PC) right from medicinal herbal products and weight loss plants. Additionally, this assessment also sheltered the standard strategies and approaches which in turn is a single of the most straightforward solutions to discover antioxidant actions (AOA). So, through this analysis review we all thinking about suitable, low-cost assay simply by which included; DPPH, FCI, ORAC, FRAP, and CUPRAC assays. The results revealed that the Folin Caletu Index (FCI), ORAC, and CUPRAC had been related correlated highly with FRAP. Which means that the total phenolic contents (TPC) of NP happen to be correlated remarkably with the AOA measured by these three methods? Consequently, the FRAP, CUPRAC, and FCI assays, which in turn are considerably more affordable and less hard, had been set up to have the same predictive vitality as ORAC on NP antioxidant activity. Consequently, some NP generally recognized as slightly acidic which may have obtained from appropriate methods of antioxidant capacity detection. This due to the mechanism of electronic transfer based (ETB) on the selection of working pH, physiological pH, and alkaline and acidic pH. Finally, this review paper revealed an updated and wide-ranging summary on antioxidant extraction, characterization, analysis and identification in addition to their polyphenolic activities. Moreover, the anticancer effects of phenolics in vitro and mechanism action have been viewed, involving recent human intervention studies. Thus, mechanisms of action including antioxidant and pro-oxidant properties as well as interfering with cellular functions are well discussed.